State of cerebral venous hemodynamics in patients with chronic cerebral ischemia and its correction - Iarkova, S. V. (Zaporozhye Medical Journal, 2014)
Aim.Relevance of the study of cerebrovascular disease is caused by its high incidence and severity of complications. Methods and results. In order to improve the diagnostic and therapeutic arrangement 86 patients with circulatory encephalopathy (DE ) II stage were examined. 62 of them were sick with dyscirculatory encephalopathy (DE) II stage. They were divided in two groups by the way of treatment mode. Namely, treatment mode with using of L-arginine in the main set and without using it in the control set. The study of cerebral hemodynamics of the patients was carried through the duplex scanning of extra- and intracranial arteries. Conclusion. The findings suggest that patients with ED II after treatment with L-lysine aescinate and diosmin had a significant improvement in cerebral venous hemodynamics and subjective better feelings.